Optimizing perioperative anesthesia strategies for safety and high-quality during painless gastrointestinal endoscopy diagnosis and treatment - Xu, Le; Li, Yanhong; Zheng, Hong; Wang, Rurong (ANESTHESIOLOGY AND PERIOPERATIVE SCIENCE, 2024)
With advancements in sedation techniques,painless gastrointestinal endoscopy has expanded from a diagnostic role to surgeries. This study aims to explore strategies for enhancing patient satisfaction, improving safety, and reducing complications. Tailoring preoperative assessments beyond American Society of Anesthesiologists classification is crucial, especially for the elderly and pediatric populations. Integration of scales and point-of-care testing (POCT) provides a precise baseline evaluations. Optimizing anesthetic strategies through improved drug selection and enhanced perioperative monitoring follows accurate patient evaluations. While post-procedural follow-up is essential, existing studies in this area are limited. This article outlines current painless gastrointestinal endoscopy technology, emphasizing POCT establishment, personalized monitoring, and optimized anesthesia strategies for a positive impact on patient outcomes.